2018
DOI: 10.1093/gerona/gly030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nutritional Intervention in Elderly After Hip Fracture: A Multicenter Randomized Controlled Trial

Abstract: BackgroundMalnutrition after hip fracture is associated with increased rehabilitation time, complications, and mortality. We assessed the effect of intensive 3 month nutritional intervention in elderly after hip fracture on length of stay (LOS).MethodsOpen-label, randomized controlled trial. Exclusion criteria: age < 55 years, bone disease, life expectancy < 1 year, bedridden, using oral nutritional supplements (ONS) before hospitalization, and cognitive impairment. Intervention: weekly dietetic consultation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(99 citation statements)
references
References 28 publications
3
85
0
Order By: Relevance
“…Other studies in hip fracture patients found mean protein intakes ranging from 43 to 57 g [33][34][35]62], which are comparable to our findings (55 g). In these studies energy intakes were also low (mean intakes ranged from 1025 to 1304 kcal versus 1319 kcal in the current study) [33][34][35]62]. Since the intake of protein and energy were low (overall low intake of food), the intakes of many other nutrients were low as well.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Other studies in hip fracture patients found mean protein intakes ranging from 43 to 57 g [33][34][35]62], which are comparable to our findings (55 g). In these studies energy intakes were also low (mean intakes ranged from 1025 to 1304 kcal versus 1319 kcal in the current study) [33][34][35]62]. Since the intake of protein and energy were low (overall low intake of food), the intakes of many other nutrients were low as well.…”
Section: Discussionsupporting
confidence: 91%
“…Such low protein intake can further induce a decline of muscle and bone mass, a higher hip fracture risk and a poor nutritional status [26,61]. Other studies in hip fracture patients found mean protein intakes ranging from 43 to 57 g [33][34][35]62], which are comparable to our findings (55 g). In these studies energy intakes were also low (mean intakes ranged from 1025 to 1304 kcal versus 1319 kcal in the current study) [33][34][35]62].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The hypothesis of the investigators was that an improvement of the malnutrition would improve the clinical outcome. As was pointed out in the Netherlands statement, and has usually been observed in RCTs in which both nutrition and clinical outcomes have been assessed (including this trial), this has not typically been the case. Various methods of providing nutrition support (including oral supplements) commonly improve nutrition status (at least with regard to energy and protein intake, body weight, and nitrogen balance), but mortality and various morbidities are, in general, not similarly affected.…”
mentioning
confidence: 90%